The confession as a 'practice of freedom' : feminism, Foucault and 'elsewhere' truths - R. Mills (Law Text Culture, 1995)
When a man comes before his judges with nothing but his crimes, when he has nothing to say but "this is what I have done," when he has nothing to say about himself, when he does not do the tribunal the favor of confiding to them something like the secret of his own being, then the judicial machine ceases to function (Foucault, 1978:18). This paper places Foucault's discussion of the confession as an uncovering of the truth of the self alongside his ideas of an aesthetics of existence in what might be considered a 'limit' case: a case in which a woman, along with three other women, is accused of killing a man previously unknown to her. The intention here is to read two separate confessions as discourses of both subjection and subjectivity; of pathology and ethics; as uncovering the truth, and as reinventing the truth. My first reading considers the confession in its most ancient form: the coupling of confession and torture; the 'dark twins of history' (Foucault, 1976:59). I will consider the repositioning of this coupling of confession and torture as forensic practice in the geographical and historical present. My second reading concerns the confession as a reinvention of truth and self. Following a brief discussion of Foucauldian notions of resistance and ethics and their relevance for feminism, I would like to consider the potential for reading these confessions as a 'practice of freedom' in and through the reinvention of the ethical self (Foucault, 1991:3-20). I am not looking for the Truth of these confessions. Rather, I am interested in their truth effects; their potential for creating various trtlths.